Olhares de professores de ciências em formação sobre as mídias, sua inserção no ensino e a educação para as mídias - Pezzo, Mariana Rodrigues (Universidade Federal de São Carlos, 2016)
In contemporary society, pervaded by media culture, the school permanently interacts with the media and information and communications technologies. In specific regard to science education, teachers and students are in contact with science information and thus representations of science and technology present in the media, either in their everyday lives outside of school, either by intentional inclusion in pedagogical practice. However, consolidated policies for media treatment by educational systems at different levels do not exist in Brazil yet. Among other elements that hinder this consolidation, lack of media education programs in teacher training, especially in undergraduate courses in science, is identified as a major obstacle. Thus, the research reported in this paper seeks to contribute to the transformation of this scenario, through the understanding of how students pursuing a licentiate degree in Biology, Physics and Chemistry relate to the media and what their expectations for the insertion of media productions at school are. In order to achieve this objective, we analyzed textual productions developed by these students within a course about the the use of science diffusion media productions in science education, in the light of a media education framework that, with contributions of Critical Theory and Cultural Studies, supports the relevance of considering media production as a social process and thus reflections and simultaneous and articulated analysis of the media industry, the media texts and the audiences and reception processes, as well as training for the use of media as selfexpression tools, creativity and resistance. The investigation process was a qualitative one, characterized as a documentary analysis carried out based on the methodological framework of discursive textual analysis. The results indicate some aspects worthy of special attention in structuring media education policies and programs in teacher training, including the permanence of prospects of media education as protection and not as a preparation for autonomous, critical and creative access and use of media; the understanding of media as a social process detached from other processes of reproduction and transformation within our societies; and the need for further reflection and advances in achieving articulation between the uses of media in science education as sources of content, pedagogical tool and object of study in its analytical and creative dimensions.
Keywords: Educação para as mídias; Ensino de ciências; Formação de professores; Media education; Science Education; Teacher Training; CIENCIAS HUMANAS::EDUCACAO